Acoustic modelling of surface sources. Part III. Piston model, error of the model, axisymmetrical problem - BRAŃSKI, A. (Archives of Acoustics, 1995)
Two piston models of a plane axisymmetric source were compared. In the first of them, the constant vibration velocities of the elements were calculated as an integral mean value of the assumed vibration velocity. However, in the other, as arithmetic mean value of discrete values of vibration velocity. These models were compared for arbitrary discretization and for optimal one. For both models numerical experiments were carried out, first of all, as a function of the number of the discrete values of vibration velocity and the next as a function of nondimensional wave number. Numerical examples pointed out the parameters of such a source for which a "good" piston model may be built based on several discrete values of vibration velocity.